Computer Modeling in Archaeology: The Case of Bronze and Iron Age Monumental Constructions of Armenia - Hayk Avetisyan; Artak Gnuni; Levon Mkrtchyan; Arsen Bobokhyan (Banber Arevelagitut'yan Instituti)
The given contribution is devoted to the problem of computer modeling in archaeology. The territory of the Republic of Armenia is chosen as a target zone for investigations, which is considered in the context of historical and cultural developments of the neighboring countries. The chronological range of the given study is the Bronze and Iron Ages (3rd-1st millennia BC). Тhe principles of computer modeling are applicable to the investigation of monumental architecture (fortifications, towers, cairns, kites, kurgans, dolmens), aiming at reconstructing both the complexes of the monuments and the historical landscape.